2020
DOI: 10.21203/rs.3.rs-93204/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Maternal and Child Health Implementation Research in Mozambique: Effective Community Interventions to Promote Sexual and Reproductive Health

Abstract: Background: High maternal and neonatal mortality rates in Mozambique, are due to adolescent pregnancies, difficulties in accessing health services, traditional constraints, and gender inequalities. An implementation research project, Alert Community to Prepared Hospital in Natikiri, Nampula, Mozambique was developed to reduce maternal and new-born mortality. From 2016 to 2020, it implemented activities to improve population knowledge and function in sexual and reproductive health, and to enable community parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(19 citation statements)
references
References 14 publications
0
19
0
Order By: Relevance
“…The teaching about respecting one's partner is mentioned by 13 interviewees: respecting the difference, respecting the partner when getting married, taking good care of each other and the house, knowing how to talk about problems, not cheating, when the woman doesn't want to have sex, she shouldn't be forced to; however, this orientation is stronger for the woman in relation to the man. Four interviewees (one woman) do not address this issue [3].…”
Section: Resultsmentioning
confidence: 99%
“…The teaching about respecting one's partner is mentioned by 13 interviewees: respecting the difference, respecting the partner when getting married, taking good care of each other and the house, knowing how to talk about problems, not cheating, when the woman doesn't want to have sex, she shouldn't be forced to; however, this orientation is stronger for the woman in relation to the man. Four interviewees (one woman) do not address this issue [3].…”
Section: Resultsmentioning
confidence: 99%
“…Studies were published between 2020 and 2023 solely in English. Overall, 14 studies reported data from four low-income countries (34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46)(47), 21 studies were focused on 13 lower-middle income countries , seven studies were conducted in five upper-middle income countries (69)(70)(71)(72)(73)(74)(75) and three were multi-centred (76)(77)(78). Out of 45 included studies, 11 studies were cross-sectional (41, 45, 48, 51, 55-57, 65, 69, 70, 76), 14 were pre-post studies (34,38,49,50,52,53,56,62,64,(72)(73)(74)(75)77), nine were time-series (35,37,39,43,58,59,67,71,78), five were mixed methods (36,…”
Section: Overview Of Included Studiesmentioning
confidence: 99%
“…Included studies showed mixed results concerning institutional deliveries that comprise normal vaginal deliveries and caesarean sections. Even though eight studies highlighted a reduction in the number/proportion of institutional deliveries (36, 49-51, 56, 61, 62, 67, 71), six reports (38,43,63,(73)(74)(75) observed growth and two studies (34, (36,62) and reduced in Ghana (48).…”
Section: Impact On Institutional Deliverymentioning
confidence: 99%
See 2 more Smart Citations